Trends in the incidence and prevalence of end-stage renal disease with hemodialysis in entire Korean population: A nationwide population-based study. Issue 13 (2nd April 2021) - Choi, Hong Sang; Han, Kyung-Do; Oh, Tae Ryom; Suh, Sang Heon; Kim, Minah; Kim, Chang Seong; Bae, Eun Hui; Ma, Seong Kwon; Kim, Soo Wan
Abstract : Abstract: Data on the overall epidemiology and temporal trends of end-stage renal disease (ESRD) requiring hemodialysis in Korea are scarce. We aimed to estimate the prevalence and incidence of ESRD requiring hemodialysis in Korea between 2002 and 2017. Using the National Health Insurance Service database, we analyzed data from the entire Korean population between 2002 and 2017. Hemodialysis patients were identified using rare incurable disease codes (V001) or prescription of medical fee codes of hemodialysis (O7020 and O7021). We only included patients who had been maintained on hemodialysis for more than 90 days from the date of dialysis initiation, to exclude patients who required short-term dialysis for acute kidney injury, conversion to peritoneal dialysis, or kidney transplantation. During the 16-year follow-up, the number of hemodialysis patients in Korea has steadily increased from 11, 215 in 2002 to 67, 486 in 2017. The mean age of these patients has gradually increased from 55.57 ± 13.31 years in 2002 to 62.13 ± 13.23 years in 2017. In 2017, the crude prevalence rate of hemodialysis was 1303.4 per million population. Overall, the number of men tended to be somewhat higher than that of women, and the proportion of men increased slightly from 55.56% in 2002 to 58.45% in 2017. The proportion of diabetic patients increased rapidly from 23.84% to 47.84%, and the percentage of dyslipidemic patients rose from 18.9% to 86.7%. The number of incident hemodialysis patients increased significantly from 4406 in 2003 to 12, 134 in 2014, and then decreased to 8090 in 2017. In the incident cases of hemodialysis, the observed increase in the proportion of male patients and in diabetes and dyslipidemia were similar to that of prevalent patients. The more recent era of hemodialysis initiation, the better 5-year survival rates were observed. The prevalence and incidence of hemodialysis in Korea gradually increased between 2002 and 2017. The proportion of men, and patients with diabetes and dyslipidemia requiring hemodialysis also increased continuously. The survival rate of hemodialysis patients was gradually improving. These findings may serve as a reference for future epidemiological studies on hemodialysis in Korea. Abstract : Supplemental Digital Content is available in the text